Processos de catálise e adsorção, em fase líquida, de hidrocarbonetos poliaromáticos sobre alumino e titanossilicatos mesoporosos - Araújo, Rinaldo dos Santos (2005)
Mesoporous materials containing aluminum and titanium were obtained by direct synthesis at room temperature, using a sol-gel method with two reaction steps (acid and alkaline hydrolysis). After solvent extraction and calcination (550 °C) the solids were labeled HMCM-41, Al-MCM-41(10), A1-MCM-41(30) and Ti-MCM-41(40). The numbers in parenthesis denotes the Si/metal molar ratio of the structure. A hexagonal mesoporous silica containing titanium, Ti-HMS(30), was also prepared, using primary dodecylamine as a template at pH 10. The total preparation time in both procedures was less than 17 h. This includes an aging phase of the synthesis liquor. The net synthesis yields were higher than 40 %, which makes this method very promising. Characterization analyses were made by infrared spectroscopy, therinogravimetry, X-Ray diffraction, textural analysis by N2 adsorption at 77K, light scaterring, XPS spectroscopy, and measurements of superficial acidity and chemical analysis (ICP, EDX). The results indicate samples with reasonable crystallinity, surface areas of 500-750 m2/g, high isomorphic substitution degree and, in certain cases, acidity (Brtinsted and Lewis) superior to a commercial Y zeolite (Si/A1 = 1,5). Catalytic studies of anthracene oxidation in liquid phase at 75 °C using tertbutylhydroperoxide as oxidant agent showed that the Ti-HMS(30) sample is much more prone to produce 9,10-anthraquinone (> 90 %) then the other mesoporous samples. This performance is directly related to parameters such as diameter and thickness of the porous wall, molar ratio Si/Ti and location, concentration and nature of the Brtinsted and Lewis acid sites. The reaction kinetics experiments show a great dependency of specific reaction rates with temperature (in the range 47-75 °C) and activation energy value of 15.2 kcal/mol. This indicates that the controlling step is either the diffusion within the pores and/or the chemical reactions on the surface. The adsorptive properties of the H-MCM-41 and aluminosilicate samples for polyaromatics hydrocarbons (naphtalene, anthracene and pyrene) were also studied at 25, 40 and 60 °C. The Langmuir and Sips isotherms correlate well the equilibrium data, indicating increasing adsorption capacity (q,n) in the following order: Al-MCM-41(10) > Al-MCM-41(30) > H-MCM-41. Such behavior suggests an adsorption process entirely explained by the interaction between the 7c-electrons of the aromatic rings and the silanol groups present on the surface. The best qm result was obtained for pyrene adsorption in AlMCM-41(10), with a value of 1.83 mmol/g. For the aluminosilicates, the adsorption capacity is slightly influenced by the amount of incorporated Al. In general, the results confirm that the synthesized materials are promising catalysts (redox and acids), catalytic supports and adsorbents.